Study of SiO2- B2O3 based Glass Ceramics as Sealants - Kumar, Vishal (My University, 2010)
Glass and glass ceramics are being used in many fields of engineering and technology. Recently, glass and glass ceramics are also finding application in the field of renewable energy especially as a sealing material in solid oxide fuel cells as conventional sealing materials cannot work at the operating temperature (800-1000°C) of solid oxide fuel cells (SOFCs). In order to check the feasibility of various glasses as sealing materials it is necessary to understand the crystallization kinetics, thermal and structural properties of the glasses. In addition, chemical interaction study with other components of SOFC is must for its end application as sealing material for longer duration. Basically, glass and glass ceramics must be chemically stable, mechanically rigid after sealing and thermodynamically nonreactive to meet the prerequisite condition as required for sealing material during operation of SOFC.
Ph.D.
Keywords: sealants, glasses